An analytical and experimental performance analysis of a flat-absorber cylindrical parabolic concentrator and a flat-plate solar collector - Singh, Padam (University of Ottawa (Canada), 1978)
Abstract not available.
Keywords: Alternative Energy.; Engineering, Electronics and Electrical.; Energy.